2014
DOI: 10.4236/as.2014.513136
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Fatigue Strength and Stiffness of High-Tech Bamboo/Epoxy Composites

Abstract: A major problem in the strength data available for cellulose fibre-based materials is that the moisture content of the test specimens is rarely measured, and yet it is the dominant variable in the tests. Detailed strength and stiffness results are presented for Brazilian Dendrocalamus Giganteus bamboo at a wide range of moisture contents down to 2% and the fatigue curve is given for Chinese Moso bamboo at 4% moisture content. Techniques are described for handling the variability of these natural materials, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In another work by Shah et al (2013) the S-N curves of different plant fiber/yarn polyester composites showed similar trends. However, a high-tech bamboo/epoxy composite made from Chinese Moso bamboo is reported to reach a 80 MPa fatigue limit (Platts 2014). In the composite, the transition region could have a slight influence on the fatigue data. The transition region is normally can be related to the types of damage that the composite experiences.…”
Section: Fatigue Resultsmentioning
confidence: 99%
“…In another work by Shah et al (2013) the S-N curves of different plant fiber/yarn polyester composites showed similar trends. However, a high-tech bamboo/epoxy composite made from Chinese Moso bamboo is reported to reach a 80 MPa fatigue limit (Platts 2014). In the composite, the transition region could have a slight influence on the fatigue data. The transition region is normally can be related to the types of damage that the composite experiences.…”
Section: Fatigue Resultsmentioning
confidence: 99%
“…Holmes et al [ 161 ] produced a novel bamboo-poplar epoxy laminate for blades formed by hot-pressing and carried out mechanical testing of the laminates (monotonic tensile and compressive stress-strain behavior and tension-tension fatigue life). Platts [ 162 ] presented strength test results for Brazilian Dendrocalamus Giganteus bamboo. He demonstrated the important effect of the moisture content on strength and stiffness and proposed to coat the bamboo with epoxy resin, to create a vapor barrier and preserve the dryness.…”
Section: Preventing Composite Wastes-2: Bio-based Compositesmentioning
confidence: 99%
“…Therefore, a combination of two materials with natural fibers produces a stronger and more corrosion-resistant material. It also improves the stiffness, strength and moisture-resistant behavior of the composites (Aidy et al, 2016;Verma and Chariar, 2012;Porras and Maranon, 2012;Yeh and Lin, 2012;Yao and Li, 2003;Li et al, 2002;Van der Lugt et al, 2006;Obataya et al, 2007;Shao et al, 2010;Biswas and Satapathy, 2010;Liu et al, 2012;Anwar et al, 2009;Darshil et al, 2013;Harris, 2003;Toshihiko et al, 2014;Amada and Untao, 2001;Platts, 2014). A review of bamboo research findings is presented in the works of Rassiah and Megat Ahmad (2013a, b).…”
Section: Introductionmentioning
confidence: 99%